Kompetensi Kepribadian Guru Dayah Darussalam Labuhan Haji Kabupaten Aceh Selatan - Yusran Syah Putra (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2022)
Boarding (Dayah) is the oldest educational institutions and popular areas in Aceh. Then, the teacher is one of important causes in success of implementation educational process, teacher who has responsibilities to lead the student in reaching the educational target and achievement. This research based on the unclearness of teacher competence personality at Boarding (Dayah) Darussalam Labuhan Haji south Aceh and by assumption that boarding teacher of Darussalam Labuhan Haji south Aceh is the older/senior level student who generally is not graduated from the university or teacher educational major. This research used qualitative method. The location of this research was at Darussalam Labuhan Haji Boarding south Aceh. The data technique collection used Observation, interview, and documentation. The subjects of the interview were head master, teacher and student of Darussalam Labuhan Haji Boarding school. And the analysis technique used the data reduction method, display and verification. Finally, after the analysis the data collection, shown that teacher competence personality at Boarding (Dayah) Darussalam Labuhan Haji south Aceh is good. And found some teacher’s obstacles in implementing teacher competence personality, such as the background of various languages, lack of educational tools, lack of teachers, and students various ages at certain level.